A plague of sheep environmental consequences of the conquest of Mexico - Melville, Elinor G. K.; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 1994)
This is a book about the biological conquest of the New World. Taking as a case study the sixteenth-century history of a region of highland central Mexico, it shows how the environmental and social changes brought about by the introduction of Old World species aided European expansion. The book spells out in detail the environmental changes associated with the introduction of Old World grazing animals into New World ecosystems, demonstrates how these changes enabled the Spanish takeover of land, and explains how environmental changes shaped the colonial societies.
Introduction -- Alien landscapes -- The Australian experience -- The Mexican case -- The conquest process -- The colonial regime.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Electronic books; Sheep -- Ecology -- Mexico -- Mezquital Valley (Hidalgo) -- History -- 16th century; Animal introduction -- Environmental aspects -- Mexico -- Mezquital Valley (Hidalgo) -- History -- 16th century; Grazing -- Environmental aspects -- Mexico -- Mezquital Valley (Hidalgo) -- History -- 16th century; Pastoral systems -- Environmental aspects -- Mexico -- Mezquital Valley (Hidalgo) -- History -- 16th century; Human ecology -- Mexico -- Mezquital Valley (Hidalgo) -- History -- 16th century; Indians of Mexico -- Mexico -- Mezquital Valley (Hidalgo) -- History -- 16th century; Mezquital Valley (Hidalgo, Mexico) -- Environmental conditions -- History; Mexico -- History -- Conquest, 1519-1540.; Mexico -- History -- Spanish colony, 1540-1810.